Menjadi Manusia Seutuhnya: Menelisik Tegangan Identitas Remaja Kristen di Era Digital - Blegur, Romelus (Sekolah Tinggi Teologia dan Filsafat Widya Sasana, 2025)
Adolescents are individuals who are experiencing identity tension between childhood and adulthood. They face a challenging transition phase to strengthen their sense of self, making them easily influenced by various factors in an effort to gain self-recognition. This presents a challenge for them in navigating digital culture, with its unstoppable and uncontrolled openness to all kinds of information. The purpose of this study is to investigate the problems faced by Christian adolescents in facing identity tension amidst the changing times and to provide solutions to overcome these problems and shape them into whole human beings amidst the challenges of digital culture. The method used is a library research method with references to literature related to the research topic. In this regard, the author conducted a review of 33 pieces of literature consisting of 30 journal articles and 3 reference books. The results of this study indicate that to become a whole human being in this digital era, it is necessary to develop intellectual intelligence, foster social and emotional maturity, and foster spiritual-ethical maturity. These principles are important to prevent adolescents from developing false identities in cyberspace and the artificiality projected by the digital era. This formation also includes intensive mentoring as a practical step by increasing the strengthening of Christian values with methods that are relevant to the youth context.